The Influence of Entrepreneurship Capability to Micro and Small Business Growth in Indonesian Fish Processing Industry - Ratnaningtyas, Sudrajati; Sutardi, Acip; Makbul, Yogi (International Journal of Engineering and Technology, 2018)
This study aims to measure the entrepreneurship capability and its influence on business growth in the fish processing industry which is a supporter of the culinary industry. There are three dimensions of entrepreneurship capability included in the model: entrepreneurial skills, management skills, and technical skills, with each factor. The research was conducted in fish production center in West Java Indonesia, in 2017. The research method used was survey method by Two-Stage Cluster Random sampling technique; and used primary and secondary data. Data analysis technique used Compound Annual Growth Rate (CAGR) to measure business growth, and Structural Equation Model (SEM) to analyze the influence of entrepreneurship on business growth. The results showed that communication, ability to take risk, innovative, change-oriented, persistent, proactiveness, committed, planning and goal setting, decision making, motivating, marketing, inner control, design, environment observation, critical path method, work break down structure are indicators appropriate to be a measure of entrepreneurial capability, especially for micro and small business manager. Entrepreneurship capability significantly influenced business growth at 95 percent confidence level. It means that when entrepreneurship capability is improved it will increase the business growth rate of micro and small business in the fish-based food processing industry in Indramayu Regency.Â Â